Interrelationship between ectoparasites and wild rodents from northeastern Buenos Aires province, Argentina - Nava, Santiago (2003)
Infestation parameters and indices of mites, ticks and fleas associated with wild rodents from northeastern Buenos Aires Province, Argentina, were studied. Host species similarity was also analyzed in relation to their ectoparasites. Fifty-five rodents were captured from January 2000 to March 2001. In total, 1,022 ectoparasites were collected and three ectoparasite-host associations were new records. However, this is the first study on Craneopsylla minerva wolffhuegeli infesting parameters. Ectoparasite total mean abundance and total prevalence were higher in Holochilus brasiliensis (MA = 47.7; P = 100%) and Scapteromys aquaticus (MA = 25.4; P = 95.4%), meanwhile specific richness and diversity were higher in Oligoryzomys flavescens (S = 6; H = 1.3) and Akodon azarae (S = 4; H = 1.0). On the other hand, the only individual of Calomys laucha was not parasited. S. aquaticus-H. brasiliensis, which preferred similar microhabitats, shared the same ectoparasite species (Css = 100). Whereas, A. azarae, which was mostly associated with grassland, showed the highest difference with the other hosts (Css < 0.4). Considering every ectoparasite species, H. brasiliensis showed the highest mean abundance, prevalence and preference. The results suggest that the particular characteristics of this rodent would give it better possibilities not only of being infested by ectoparasites, but also of transmitting them to its progeny.